Implementation of a Mamdani Fuzzy Inference System for Assessing Students’ Stress Levels in Final Project Completion (A Case Study of the Informatics Engineering Study Program at UMI) - Ririn Melani Asaf; St. Hajrah Mansyur; Siska Anraeni (ISB Atma Luhur, 2026)
Academic stress among Informatics Engineering students at Universitas Muslim Indonesia during final project preparation can negatively affect academic performance and mental well being. This study aims to apply the Mamdani Fuzzy method to support the measurement of student stress levels by processing uncertain information through fuzzy sets, rule-based inference, fuzzification, aggregation, and defuzzification. The proposed approach is used to identify student stress levels, classified into Low, Medium, or High, based on several academic variables, including research topic selection, references, time management, consultation with supervisors, data processing, and technical constraints. System testing indicates that the MATLAB implementation produces an output value of 1.66, while manual calculation results in 1.6344, showing a small difference of 0.03. Both results classify the stress level as Low, suggesting that the Mamdani fuzzy approach yields consistent outcomes and demonstrates potential as a supportive tool for assessing academic stress.